Relationship Between Quality Management And Productivity In The Company Constructora Kaliss, Juliaca – 2022 - Haydeé, Guzmán Ramos; Margot, Yucra Pari Yasheni (Migration Letters, 2024)
The general objective of the following research was to "determine the relationship between quality management and productivity in the construction company Kaliss, Juliaca-2022". The present inquiry belongs to the quantitative approach, with typology of applied research, non-experimental research design of transversal cut, constituted by 20 workers, executed with a non-probabilistic sampling by convenience, it was carried out with a technique the questionnaire of 20 items, achieving as a result the quality management and productivity in the construction company Kaliss with a result of rs = 0.667, where it indicates that if there is moderate positive correlation between existing variables of research. Accordingly, between quality management and productivity efficiency in the Kaliss construction company the Spearman’s Rho correlation coefficient shows the result of rs = 0.577; which indicates that there is moderate positive correlation between the research variables. Finally, there is enough evidence that there is a relationship between quality management and productivity efficiency in the Kaliss construction company with the result rs= 0.512; which affirms that there is a moderate positive correlation between the study variables. Finally, it was concluded that there is a relationship between quality management and productivity in the Kaliss company, with a level of 5% significance. Therefore, we recommend that priority should be given to the use of quality standards (ISO 9001) and productivity in companies will increase.